The Roles of 2-Hydroxyglutarate - Du, Xin; Hu, Hai (Frontiers in Cell and Developmental Biology, 2021)
2-Hydroxyglutarate (2-HG) is structurally similar to α-ketoglutarate (α-KG), which is an intermediate product of the tricarboxylic acid (TCA) cycle; it can be generated by reducing the ketone group of α-KG to a hydroxyl group. The significant role that 2-HG plays has been certified in the pathophysiology of 2-hydroxyglutaric aciduria (2HGA), tumors harboring mutant isocitrate dehydrogenase 1/2 (IDH1/2mt), and in clear cell renal cell carcinoma (ccRCC). It is taken as an oncometabolite, raising much attention on its oncogenic mechanism. In recent years, 2-HG has been verified to accumulate in the context of hypoxia or acidic pH, and there are also researches confirming the vital role that 2-HG plays in the fate decision of immune cells. Therefore, 2-HG not only participates in tumorigenesis. This text will also summarize 2-HG’s identities besides being an oncometabolite and will discuss their enlightenment for future research and clinical treatment.